Habilidades metacognitivas y hábitos de estudio en estudiantes de psicología de Riohacha, descritos desde un enfoque diferencial cultural (2022)
This research evaluated the relationship between metacognitive skills and study habits in psychology students at the Antonio Nariño University, Riohacha, described from a cultural differential approach, with metacognitive skills being reflective processes that a person has about their own knowledge. (Huertas, 2014) and study habits, behavior that is acquired by repetition or learning until it reaches automation (Villamizar et al., 2019)